Teachers’ and Students’ Views on the Readability and Comprehensibility of Texts in Secondary School Mathematics Textbooks - Gökhan Çetinkaya; Arzu Aydoğan Yenmez; Tuğba Çelik (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
It is not only the student's responsibility to understand a text.Whether or not the texts presented to students are prepared in accordance withtheir level directly affect the comprehensibility of the text. Many formulashave been developed to measure the readability of texts. The sentence length isone of the important variables in the readability formulas. The case studymethod was used in this study and 5th, 6th, 7th,8th grade mathematics textbooks which were published by privatepublishers and approved by Ministry of National Education in 2017-2018 academicyear were analyzed. In this context, the relationship between the readabilityscores of the texts at the level of knowledge, questions and solutions in themiddle school mathematics textbooks and the comprehensibility of these textswere investigated. In this regard, the views of 18 mathematics teachers and 181students at the 5th, 6th, 7th and 8thgrades were taken on the comprehensibility of low, medium and high readabilityof knowledge texts, questions and solution texts. The students generally foundthe texts to be readable at a level that would not obstruct the understanding,and the teachers found it to be easily understandable. On the other hand, thestudents generally found the texts to be understandable at the medium and goodlevel and generally understandable. Results showed that, teachers, except forthe structure of the text in the middle school textbooks, want to; be increasedthe number of the daily life problems; be reduced the use of intensive symbols,and be increased the problems that are appropriate for their age andexperience. Moreover, the students, except for the structure of the text in themiddle school textbooks, want to be used multiple representations.